Statistical learning in the absence of explicit top-down attention. (October 2020) - Duncan, Dock; Theeuwes, Jan
Abstract: Recently it has been shown that statistical learning of regularities presented in a display can bias attentional selection, such that attentional capture by salient objects is reduced by suppressing the location where these distractors are likely to appear. The role of attention in learning these contingencies is not immediately clear. Specifically, it is not known whether attention needs to be directed to the contingencies present in the display for learning to occur. In the current study we investigated whether participants can learn statistical regularities present in the environment even when these regularities are not relevant for the participant and are not part of their top-down goals. We used the additional singleton paradigm in which a color singleton was presented much more often in one location than in all other locations. We show that after being exposed to these regularities regarding the location of the color singleton during an unrelated task in which there are no targets nor distractors, participants showed a suppression effect from the previously learned contingencies when switching to a task in which they search for a target and suppress a distractor. We conclude that visual statistical learning can occur in the absence of top-down attention.